UPAYA PENINGKATAN KINERJA TENAGA PENDIDIK MELALUI MONITORING DAN EVALUASI DI AKADEMI KEPERAWATAN RUMKIT TKT. III TELING MANADO PROVINSI SULAWESI UTARA - Rahmawati Sururama (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2019)
the purpose of this study was to determine the Efforts to Improve the Performance of Educators through Monitoring and Evaluation at the Academy of Nursing at the Telkkt.III Teling Manado. This research uses descriptive qualitative research method. Data Collection Techniques and Procedures, namely Observation, Interview, Documentation, while Data Analysis Techniques used in this study were based on what was developed by Strauss and Corbin (1990: 57) through several procedures, namely: Open coding, coding centralized (axial coding), and selective coding (selective coding). The results obtained from this study are as follows: Monitoring and evaluation can motivate educators to improve their performance; at the same time with Monitoring and Evaluation can be found out the way to prevent the occurrence of irregularities or mistakes by educators; Monitoring and Evaluation can increase the sense of responsibility for teaching staff in carrying out their main duties and functions as instructors. As an evaluation material for future improvement, in this study we can draw the conclusion that the improvement of performance and responsibility for the main tasks and functions for educators is the responsibility of educators and educational institutions so that deviations or mistakes can be avoided. Keywords: efforts, performance, monitoring and evaluation